24-Week Exposure to Oxidized Tyrosine Induces Hepatic Fibrosis Involving Activation of the MAPK/TGF-β1 Signaling Pathway in Sprague-Dawley Rats Model. (14th December 2015) - Li, Zhuqing Leslie; Shi, Yonghui; Le, Guowei; Ding, Yinyi; Zhao, Qi
Abstract : Scope . Oxidized tyrosine (O-Tyr) has been widely detected in many consumer protein products. O-Tyr products such as dityrosine (Dityr) and 3-nitrotyrosine (3-NT) are universal biomarkers of protein oxidation and have been demonstrated to be associated with metabolic disorders in biological system. Evaluation of potential intracorporal effects of dietary O-Tyr is important since the mechanism of biological impacts induced by oral oxidized protein products (OPPs) is still limited although we have proved that some dietary OPPs would induce oxidative injury to liver and kidney. Methods and Results . The present study aimed to investigate the dose-dependent hepatic injury caused by oral O-Tyr in rats. 24-week feeding of O-Tyr enhanced aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities, increased total bilirubin (TBiL) content, and led to oxidative damage in rats liver. Besides, O-Tyr distinctly increased the phosphorylation of p38 and ERK2 MAPKs and enhanced fibrosis-related TGF- β 1 and Smad2/3 levels. Higher extracellular matrix (ECM) indexes (ICTP, PIIINP) and histological examination (HE and Masson staining) also supported dose-dependent hepatic fibrosis caused by O-Tyr. Conclusion . These findings reveal that O-Tyr may induce oxidative damage and hepatic fibrosis via MAPK/TGF- β 1 signaling pathway, in which ROS together with malondialdehyde (MDA) and OPPs act as the pivotal mediators.